Risk Factors, Attitude and Knowledge of Farmers in Controlling Anthrax - Eny Martindah (Indonesian Center for Animal Research and Development, 2017)
In terms of epidemiology, the distribution of anthrax globally remains enzootic, and is endemic in some parts of Indonesia. Contact with anthrax spores that present in meat, soil and grass can cause disease in both humans and animals. This paper describes risk factors causing high prevalence of anthrax, also attitude and knowledge of farmers’ community toward anthrax. Several risk factors that causing high prevalence of anthrax transmitted to humans are lack of farmers’ knowledge on anthrax, people's habit of slaughtering the sick animal and consuming the meat for economic reason. The knowledge of anthrax amongs farmer communities are influenced by education level, information sources, and professions. Farmers community knowledge in Indonesia towards anthrax is relatively low. Most farmers have wrong perception that anthrax is non-contagious disease. Control of anthrax in livestock and humans will be effective, if the community has better knowledge, attitude and good perception of disease. Interventions need to consider both technical and social (local knowledge and culture, as well as community behavior) factors to be appropriate and more acceptable to farmers and local communities.